Analisis Kesehatan Keuangan Bank Syariah Mandiri Ditinjau dari Faktor Permodalan (CAR), Pembiayaan (FDR), Profitabilitas (ROA & ROE) Serta Risiko Kredit (NPF) - Awan Kostrad Diharto (ITB AAS INDONESIA Surakarta, 2020)
The aims of the research is to find out the financial soundness of Bank Syariah Mandiri (BSM) seen from the capital factor (CAR), financing (FDR), profitability (ROA & ROE), and credit risk (NPF). This research uses quantitative descriptive methods. The data used are the 2014-2018 financial statements. The results of this study indicate that BSM in terms of capital using the CAR ratio shows an average CAR ratio of 14.75%. This means that BSM in terms of capital is ranked very well. This means that BSM's ability to generate profits is ranked quite well. Bank Syariah Mandiri in terms of financing using the FDR ratio shows an average FDR ratio of 79.81%. This means that BSM's ability to repay short-term loans and meet agreed financing is at a healthy rating. Bank Syariah Mandiri in terms of profitability using the ROA and ROE ratio shows an average ROA of 0.53% and ROE of 6%. Bank Syariah Mandiri in terms of credit risk using the NPF ratio shows an average NPF ratio of 3.18%. This means that there is very little credit provided by Bank Syariah Mandiri and the bank is viewed from the aspect of credit risk, including in a good rating. From the results of these research, indicate that the the soundness level of Bank Syariah Mandiri (BSM) is in a good level of soundness.